FEATURES OF COMBATING CRIMES OF SECRET ROBBERY OF OTHER PEOPLE'S PROPERTY - Uzokov Abbas Avazovich; A.A. Sultanov (Scholar Express Journals, 2022)
The article deals with the preventive management of the crime of secretly robbing other people's property in the internal affairs bodies. Based on military data, the author analyzed the problem based on the available scientific literature and studied the specific aspects of the management of the prevention of the crimes of secretly robbing other people's property in the internal affairs bodies.
Keywords: Internal affairs; theft; crime